The metamorphosis of the Amazon an environmental history of oil extraction in Ecuador - Feichtner, Maximilian Fritz (Cambridge University Press, 2023)
The Metamorphosis of the Amazon sheds new light on the complex history of the Ecuadorian rainforest, revealing how oil development and its social and ecological repercussions triggered its metamorphosis. When international oil giants such as Shell and Texaco started to dig for oil in remote rainforest locations, a process was born that eventually altered the fabric of the Amazon forever. Oil infrastructure paved way for a disastrous industrial and agricultural landscape polluted by the hazardous waste management of the oil industry. Adopting a unique approach, Maximilian Feichtner does not recount the established narrative of oil companies vs. suffering local communities, he instead centers the rainforest ecosystem itself - its rivers, animals, and climate conditions - and the often neglected actors of this history: the oilmen and their experiences as people affected by a pollution they perpetrated and witnessed. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details